What a difference peers can make: The impact of social (work) norms on unemployment duration - Andreia Tolciu (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2009)
This article outlines a model of how social interactions among persons belonging to the same region might influence the individual unemployment duration. The impact is assumed to be enhanced through social work norms shared by peers within the group. Building on a range of German data sets and derived from multilevel analysis, the results show that social interactions in terms of social work norms, in conjunction with socio-demographic and regional characteristics, affect the individual unemployment duration.
Keywords: A13; A14; J64; Z13; 330; regional social interactions; social work norms; group influence; regional unemployment; religious influences